An Investigation of Processes of Children's Digital Technologies Usage from the Perspective of Digital Age Parents - Nesrin Hark Söylemez (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The developments in digital technologies and their widespread use among children day by day bring the need to investigate the processes of children's use of digital technologies. The purpose of this study is to investigate the processes of children's digital technologies usage from the perspective of digital age parents. The phenomenology pattern is used to conduct the study. The study group consists of 15 parents, selected according to the criterion sampling. A semi-structured interview form is used as a data collection tool. Content analysis is used in the analysis of the data. It is found that the majority of parents do not find digital environments safe. Parents stated the negative effects of digital technologies on children as developing various addictions, health problems, decline in academic success, decline in face to face communication skills, moving away from real life experiences, and moving away from cultural values. The majority of parents indicated that they did not witness a negative event that their children experienced in digital environments. Another important result is that the majority of children do not seek help from their parents regarding the problems they encounter in digital environments. It is recommended that parents should create an environment of trust where their children can share their negative situations and establish a strong communication with their children.